Myrcia sect. Calyptranthes (Myrtaceae) from the Atlantic Forest, Brazil - Lourenço, Ana Raquel; Burton, George P.; Alves, Marccus; Lucas, Eve (Phytotaxa, 2020)
Myrcia sect. Calyptranthes is a section of the Neotropical genus Myrcia ranging from Mexico and the Caribbean to northern Argentina with ca. 260 known species. In Brazil ca. 78 species are known, of which ca. 53 are endemic, occurring mainly in the Atlantic and Amazon domains, with few species in the Caatinga and Cerrado. This paper is a taxonomic revision of 38 species from the Atlantic Forest including one newly described species Myrcia botryophylla. The treatment provides an identification key, taxonomic descriptions, phenology and geographic distribution information, nomenclatural updates, synonymy, and illustrations of the main morphological characters. The main character used for differentiating species is inflorescence pattern, but observation of several further characters including leaf size and shape, flower buds and indument assists in species determination. Of the 38 species recognized 29 are endemic to the Atlantic Forest domain and 9 occur in the Amazon, Cerrado and/or other habitats in South and Central America. Twenty-two new synonyms are proposed, two new combinations are made and 29 lectotypes are designated. One new species is described.